Shame, Catastrophizing, and Negative Partner Responses Are Associated With Lower Sexual and Relationship Satisfaction and More Negative Affect in Men With Peyronie's Disease. Issue 3 (3rd April 2017) - Davis, Seth; Ferrar, Saskia; Sadikaj, Gentiana; Binik, Yitzchak; Carrier, Serge
Abstract : Peyronie's disease (PD) has a negative impact on men's sexual functioning and quality of life, but little is known about why some men cope better than others and what the effects of PD are on their relationships. The aims of the present study were to describe negative affect, pain, and relationship and sexual satisfaction in men with PD, and to explore their psychosocial correlates. Participants were 110 men diagnosed with PD. All men completed questionnaires. The main outcome measures were as follows: Global Measure of Sexual Satisfaction, Dyadic Adjustment Scale, McGill Pain Questionnaire, and Negative Affect Scale. The predictor variables were the following: Experience of Shame Scale, Body Esteem Scale, Body Image Self-Consciousness Scale, Index of Male Genital Image, a modified Pain Catastrophizing Scale, and a modified Multidimensional Pain Inventory. Although men with PD had mean sexual/relationship satisfaction and negative affect scores indicating mild impairment, there was a wide range of variation, with 42% to 52% scoring in the clinical range. Catastrophizing was significantly associated with reduced sexual satisfaction and increased negative affect and pain. Shame was also associated with increased negative affect. The significant associations of relationship satisfaction were partner responses and shame. Given the lack of curative treatment in PD, understanding why some men cope better than others may guide therapy. Shame, catastrophizing, and partner responses may be important therapeutic targets.